'Ritual and Magic' in Buddhist Visual Culture from the Bird Totem - Yan, Zhilong (Religions, 2022)
Despite numerous research findings related to medieval Chinese Buddhism, the witchcraft role of bird totems in Buddhist history has not received sufficient attention. In order to fill this gap, this paper analyzes how Buddhist monks in medieval China developed a close relationship with bird-totem worship. This relationship has been documented in Buddhist scriptures, rituals, oral traditions, biographies, and mural art. Although bird-totem worship was practiced in many regions of medieval China, this paper specifically examines the visual culture of bird totems in Tibetan and Chinese Buddhism. Furthermore, some details of this culture were recorded in Buddhist texts and images. According to these works, various bird-totem patterns and symbols are believed to be effective ritual arts used by Tibetan and Chinese Buddhist monks to influence nature and the supernatural through ritual and magic.